Processing and storage of blood components as a precondition for safe transfusion - Antić, Ana; Živković Đorđević, Sanja; Stevanović, Suzana; Jelić, Marija (Medical Word, 2020)
The preparation of blood components from whole blood collections must be standardized and compliant with recommendations, EU Directives and Standard Operative Procedures (SOPs). In order to achieve safe and efficient transfusion it is important to have automated separation of whole blood unit producing standardized blood components, good quality control and increased work efficiency. It is also very important that all blood components should be ISBT 128 labelled and properly storaged under the regulated conditions.One of the most important factors that increases transfusion safety is leucoreduction of blood components, which prevents several adverse effects following blood transfusion, as well replacement of plasma as a storage medium in red blood cells and platelet concentrates with preseravative solutions,  which results in the reduction of iso- and HLA-antibodies and plasma proteins.Pathogen inactivation in blood products is the trend of modern blood transfusion practice and acts in the removal or inactivation of all pathogens that can be blood transmitted. It does not replace testing of blood units for transfusion transmitted diseases, but it reduces the risk of “window phenomenon” and errors in testing, acting on the agents that are not included in routine testing. In circumstances where the pathogen reduction has not been introduced in practice routine bacteriological testing of blood components significantly decreases the occurence of adverse reactions on contaminated blood.Processing using the most appropriate and effective methodologies and best laboratory practices, efficient inventory management system for optimum blood stocks, and effective blood cold chain for safe storage and distribution of blood and blood products are key requirements to ensure the safety of blood  products.
Keywords: transfusion, safety, blood components